Breeding sorghum for diverse end uses - C, Aruna; Visarada, K. B. R. S.; Bhat, B. Venkatesh; Tonapi, Vilas A. (Woodhead Publishing in food science, technology, and nutrition., 2019)
'Breeding Sorghum for Diverse End Uses' is a comprehensive overview of all significant global efforts for the genetic improvement of sorghum, a major crop of many semi-arid nations that is suitable for a huge range of uses, from human food, to biofuels. Split into two main sections, the book initially reviews the genetic suitability of sorghum for breeding, also providing the history of the genetic improvement of the grain. Finally, other sections look at specific breeding programs that could be improved in a number of areas, including human food, animal feed and industrial usage. Readers in academics, research, plant genetics and sorghum development will find this resource of great value. In addition, it is essential reading for engineers who utilize sorghum for food, feed and industrial materials in industry. --